2008
DOI: 10.1111/j.1365-2222.2008.03045.x
|View full text |Cite
|
Sign up to set email alerts
|

Type III IFN‐λ mRNA expression in sputum of adult and school‐aged asthmatics

Abstract: Our results show that asthmatic subjects have substantial type III IFN-lambda mRNA levels in the airways. Our data furthermore suggest that IL-29 could have an immunoprotective role in the lower airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 23 publications
3
40
1
Order By: Relevance
“…Comparison of volunteers with and without asthma experimentally infected with an attenuated HRV showed lower type III IFN-l 1 and type III IFN-l 2 levels in respiratory secretions of patients with asthma (14). Conversely, other studies have shown elevated IFN-l 1 in people with asthma compared with people without asthmas (33,34).…”
Section: Type III Ifn-l 1 As a Determinant Of Disease Severitymentioning
confidence: 86%
“…Comparison of volunteers with and without asthma experimentally infected with an attenuated HRV showed lower type III IFN-l 1 and type III IFN-l 2 levels in respiratory secretions of patients with asthma (14). Conversely, other studies have shown elevated IFN-l 1 in people with asthma compared with people without asthmas (33,34).…”
Section: Type III Ifn-l 1 As a Determinant Of Disease Severitymentioning
confidence: 86%
“…Because epithelial and immune cells both produce and respond to IFN-l (9-11), it is likely to play an important role in the immune/epithelial interface. Aberrant interactions in this location are particularly important in the asthmatic airway (26), a condition in which IFN-l1 may be deficient (24,25). The IFN-l1 that is produced by airway epithelial cells is critical for mounting efficient antiviral responses and, in parallel, moderating Th2 development; therefore, we characterized the regulation of this gene's expression in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Further, IFN-l1 secretion is itself Th2 cytokine responsive (11,12,(21)(22)(23). Recent studies also showed that IFN-l1 expression is reduced in alveolar macrophages and bronchial epithelial cells of rhinovirus-infected asthmatic individuals (24,25). Two key contributing pathologies in asthma are the upregulation of Th2 responses and remodeling of the airway epithelial cells (26).…”
mentioning
confidence: 99%
“…However, others have found that control of viral replication and production of IFN may also be defective in airway epithelial cells from patients with other types of inflammatory airway disease, e.g., COPD and cystic fibrosis (65-67). Moreover, even in the case of asthma, not all reports agree on a defect in IFN-dependent control of viral replication ex vivo or in vivo (18,(68)(69)(70)(71)(72). A better understanding of the issue will require a comprehensive analysis of type I, II, and/or III IFN level and/or signaling activity during viral infection in asthma versus normal subjects, but this has been difficult to achieve in part because of the logistical challenge of quantifying IFN and corresponding viral load in vivo.…”
Section: Epithelial Cells and Viral Diseasementioning
confidence: 99%